Antimicrobial resistance of e. coli isolates from pig farm workers, nondiarrhoeic and diarrhoeic piglets - Choo, Pow Yoon; Abdullah, Abdul Salam; Abdul Razak, Che Nyonya (Universiti Putra Malaysia Press, 1995)
Antimicrobial resistance of 274 E. coli isolates from farm workers, nondiarrhoeic and diarrhoeic piglets to 11 antimicrobial agents was investigated to determine the antimicrobial resistance pattern of E. coli. Five pig farm were involved in this study. Antibacterial resistance was significantly higher (p>0.01) and almost 100% for Sulphasoxazole, streptomycin, and tetracylin in porcine isolate compared with the human isolate. The means percentage of antibiotic resistance between farms were not significantly different (p>0.05) irrespective of source of isolate. statistical analysis showed that the antibiotic resistance were significantly lower (p<0.05) in farm worker and isolates than in nondiarrhoeic and diarrhoeic piglet isolate. The percentage of isolate resistant to at least eight antibiotic were 27.7, 5.6 and 1.0 for isolates from diarrhoeic, nondiarrhoeic piglets and farm workers respectively. the present study also indicated that the mean antimicrobial resistance was significantly higher in larger farms (p<0.01) and in farms without a resident veterinarian (p<0.05).